2022
DOI: 10.1002/ijc.34118
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic microbiome and metabolome analyses reveal the interaction between gut microbiota andanti‐PD‐1 based immunotherapy in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a severe disease with high mortality and global incidence. However, the interaction between the gut microbiome and combined immunotherapy for HCC is yet unclear. In this prospective clinical study, patients with unresectable HCC who had not received systemic treatment previously were recruited. Fecal and serum samples were collected at the baseline point and before each subsequent administration as specified. Between 20 October 2019 and 2 February 2021, 61 patients were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Serum galactaric acid was shown to be positively correlated with Ruminococcus abundance in hepatocellular carcinoma patients responding to immunotherapy (Wu et al. 2022 ). This suggests that high galactaric acid levels are related to abnormal microbiota activities in SAP.…”
Section: Discussionmentioning
confidence: 99%
“…Serum galactaric acid was shown to be positively correlated with Ruminococcus abundance in hepatocellular carcinoma patients responding to immunotherapy (Wu et al. 2022 ). This suggests that high galactaric acid levels are related to abnormal microbiota activities in SAP.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 The enrichment of Faecalibacterium was also associated with ICB responsiveness in different cancers, involving melanoma, HCC, and NSCLC. 36 , 41 , 42 , 43 , 44 , 45 , 46 For a specific cancer type, a meta-analysis of melanoma patients revealed that the presence of Lachnospiraceae species is associated with a more favorable clinical response, while the presence of Streptococcaceae species is linked to an unfavorable response. 47 In another study, several bacterial taxa were found to be differentially enriched in melanoma patients who were responders to combined CTLA-4 and PD-1 blockade, including Bacteroides stercoris , Parabacteroides distasonis , and Fournierella massiliensis.…”
Section: Role Of the Gut Microbiome In Cancer Immunotherapymentioning
confidence: 99%
“… 52 HCC Faecalibacterium , Blautia , Lachnospiracea incertae Sedis, Megamonas , Ruminococcus , Coprococcus , Dorea , Haemophilus anti-PD-1 16S rRNA (V3-V4) 35 China Wu et al. 36 , 41 , 42 , 43 , 44 , 45 , 46 Hepatobiliary Lachnospiraceae bacterium GAM79, Alistipes sp. Marseille-P5997, Ruminococcus calidus , Erysipelotichaceae bacterium GAM147 anti-PD-1 metagenomic 65 China Mao et al.…”
Section: Role Of the Gut Microbiome In Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota also has been demonstrated to enhance the therapeutic response to immune checkpoint inhibitors though targeting immunomodulatory molecules or their ligands on the surfaces of T cells ( McCulloch et al., 2022 ; Wu et al., 2022 ; Zhang et al., 2022 ; Zhao et al., 2022 ). The combination has been approved for treating various malignant tumors, including NAFLD-associated HCC ( Baruch et al., 2021 ; Davar et al., 2021 ; Shiraishi et al., 2022 ).…”
Section: Novel Strategy For Nafld Treatment Based On Gut Microbiotamentioning
confidence: 99%